ANALYSIS OF MOTIVATION, LEADERSHIP STYLE AND WORK ENVIRONMENT TO IMPROVE EMPLOYEE PERFORMANCE AT THE REGIONAL FINANCIAL AND ASSET MANAGEMENT AGENCY (BPKAD) JEMBER REGENCY - Oktaviana, Marinda; Puspitadewi, Ira; Umamy, Septy Holisa (Jurnal Comparative: Ekonomi dan Bisnis, 2024)
Badan Pengelolaan Keuangan dan Aset Daerah (BPKAD) Jember Regency is one of the public financial institutions that functions to manage the finances and regional assets of Jember Regency, for this function, it requires high effectiveness and productivity from each employee involved. However, in reality there are still several problems related to employee performance at BPKAD Jember Regency. This study aims to determine the effect of motivation, leadership style and work environment on employee performance at BPKAD Jember Regency. This research method uses quantitative with data collection using a questionnaire. The population in this study were all employees with Civil Servant status at BPKAD Jember Regency consisting of 38 people who were used as research samples based on saturated sampling techniques. The analysis tool uses multiple linear regression. The results showed that motivation, leadership style and work environment had a significant effect on employee performance.